2020
DOI: 10.1016/j.chaos.2020.110191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of relaxation in lockdown and forecast of preparation for combating COVID-19 pandemic in India using Group Method of Data Handling

Abstract: Highlights Effect of lockdown relaxation on COVID-19 spread in India. Brief literature review of epidemic forecasting models. Model validation and standardization using actual lockdown time series. A self-organized data mining technique for forecasting active cases time series. Forecast of medical infrastructure requirement as per active cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…[18] From 18 May 2020, LD4 continued and more power were given to states to demarcate zones. The average daily number of tests have increased from 1,717 (19)(20)(21)(22)(23)(24)(25) to 131,772 (25-31 May) with an estimated testing shortfall of 4.58 million tests nationally by 31 May 2020. [19] In view of economical impacts of lockdown, relaxations in ULD1 allowed shopping malls, religious places, hotels and restaurants to reopen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] From 18 May 2020, LD4 continued and more power were given to states to demarcate zones. The average daily number of tests have increased from 1,717 (19)(20)(21)(22)(23)(24)(25) to 131,772 (25-31 May) with an estimated testing shortfall of 4.58 million tests nationally by 31 May 2020. [19] In view of economical impacts of lockdown, relaxations in ULD1 allowed shopping malls, religious places, hotels and restaurants to reopen.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that apart from relaxations in LD3 and LD4, the increased testing capacity and migration of laborers were important reasons of increased positive cases. [20] During LD5, major relaxations include opening of cinema halls with 50% sitting capacity and reopening of hill stations, beaches and national parks. The results showed that the evolution of death cases due to COVID-19 closely parallels the evolution of new cases of infection .…”
Section: Discussionmentioning
confidence: 99%
“…[18] From 18 May 2020, LD4 continued and more power was given to states to demarcate zones. The average daily number of tests have increased from 1,717 (19)(20)(21)(22)(23)(24)(25) to 131,772 (25-31 May) with an estimated testing shortfall of 4.58 million tests nationally by 31 May 2020. [19] In view of economical impacts of lockdown, relaxations in ULD1 allowed shopping malls, religious places, hotels and restaurants to reopen.…”
Section: [13]mentioning
confidence: 99%
“…Also noteworthy is the Ukrainian work by Nastenko et al [47], which used Group Method of Data Handling (GMDH) [48] models and Simplex Method [49] optimization algorithm to select the treatment strategy.…”
Section: Information Systems Of State Assessment and Forecastingmentioning
confidence: 99%